How Big We Are: Stories from Boston of Immigrant Activists in the 21st Century. - Katz-Zeiger, Daniel I. (Tufts Archival Research Center, 2014)
Abstract: How Big We Are is a documentary-style theatre piece featuring the voices of youth leading the movement towards a more just future for our nation’s immigrants. In an age when America’s youth are so often accused of apathy, mimicry and complacency, the undocumented youth movement, begun in the early 2000’s to fix the country’s broken immigration system and change a firmly established national discourse around migration and citizenship, is an important case of powerful youth agency and action. With deportations at all-time high levels, the growing militarization of immigration enforcement and the repeated failure of congress to pass a comprehensive immigration reform bill, Americans cannot continue to stand by as families are torn apart. With the aid of an accompanying classroom guide, How Big We Are can be performed and read in middle and high school classrooms to teach students about the contradictory and unjust realities of our country’s immigration policy, the ability of youths to make a real difference in their communities and the power of art as an organizing tool. It also raises important questions about the way to present discussions about race, documentation and immigration in the classroom. How Big We Are was created using a set of nine interviews conducted with activists, immigrant youth, politicians and citizens about their experience and views on immigration and immigration reform. The project built around it is an exploration in combining activist theatre and activist pedagogy with the goal of creating a curriculum capable of creating political consciousness in students.